Caesar's Civil War : historical reality and fabrication - Westall, Richard. (Mnemosyne, Supplements, 2017)
In Caesar's Civil War: Historical Reality and Fabrication , Westall combines literary analysis of Caesar's Bellum Civile with a concern for the socio-economic history of the Roman empire. The Bellum Gallicum and the Shakespearean play are better known, but Caesar's partisan account of the Roman civil war culminating in the battle of Pharsalus offers a historical text of perennial interest and relevance. Two introductory chapters contextualize this book and offer a traditional narrative of political and military history for 49-48 BCE. There follow seven chapters that are dedicated to each of the geographical theatres of civil war. These chapters show how Caesar's testimony sheds important light upon the nature of Roman rule in the Mediterranean, but also explore the problems to be encountered in using potentially tendentious testimony.